ACC1 is a dual metabolic-epigenetic regulator of Treg stability and immune tolerance - Philipp Stüve; Gloria J. Godoy; Fernando N. Ferreyra; Florencia Hellriegel; Fatima Boukhallouk; Yu-San Kao; Tushar H. More; Anne-Marie Matthies; Tatiana Akimova; Wolf-Rainer Abraham; Volkhard Kaever; Ingo Schmitz; et al. (Molecular Metabolism)
Objective: Regulatory T cells (Tregs) are essential in maintaining immune tolerance and controlling inflammation. Treg stability relies on transcriptional and post-translational mechanisms, including histone acetylation at the Foxp3 locus and FoxP3 protein acetylation. Additionally, Tregs depend on specific metabolic programs for differentiation, yet the underlying molecular mechanisms remain elusive. We aimed to investigate the role of acetyl-CoA carboxylase 1 (ACC1) in the differentiation, stability, and function of regulatory T cells (Tregs). Methods: We used either T cell-specific ACC1 knockout mice or ACC1 inhibition via a pharmacological agent to examine the effects on Treg differentiation and stability. The impact of ACC1 inhibition on Treg function was assessed in vivo through adoptive transfer models of Th1/Th17-driven inflammatory diseases. Results: Inhibition or genetic deletion of ACC1 led to an increase in acetyl-CoA availability, promoting enhanced histone and protein acetylation, and sustained FoxP3 transcription even under inflammatory conditions. Mice with T cell-specific ACC1 deletion exhibited an enrichment of double positive RORγt+FoxP3+ cells. Moreover, Tregs treated with an ACC1 inhibitor demonstrated superior long-term stability and an enhanced capacity to suppress Th1/Th17-driven inflammatory diseases in adoptive transfer models. Conclusions: We identified ACC1 as a metabolic checkpoint in Treg biology. Our data demonstrate that ACC1 inhibition promotes Treg differentiation and long-term stability in vitro and in vivo. Thus, ACC1 serves as a dual metabolic and epigenetic hub, regulating immune tolerance and inflammation by balancing de novo lipid synthesis and protein acetylation.